INTERNATIONAL TRADE AND LAW BASED ON BIBLIOMETRIC APPROACH - Willson, Joenathan; Pratono, Aluisius Hery; Budiarto, Bambang (LPPM STIE Muhammadiah Bandung, 2025)
This study applies a bibliometric approach to investigate the complex dynamics of international trade and law by analyzing a 994 academic papers. Through methods like co-citation analysis and keyword frequency analysis, the study maps the intellectual landscape of the field, revealing significant research clusters related to international law, economic growth, global trade, and human rights. The analysis uncovers emerging trends in trade law evolution, the impact of globalization, environmental sustainability, and ethical concerns in trade agreements. By highlighting key research gaps and underexplored areas, the study offers valuable insights into the intersection of political, economic, and legal frameworks that shape global trade. It demonstrates the effectiveness of bibliometric analysis in synthesizing intricate information and guiding future scholarly research in international trade and law.